Structural and optical properties of zirconia nanoparticles by thermal treatment synthesis - Keiteb, Aysar Sabah; Saion, Elias; Zakaria, Azmi; Soltani, Nayereh (Hindawi Publishing Corporation, 2016)
Zirconium dioxide nanoparticles with monoclinic blended structure were successfully synthesized by thermal treatment method using zirconium (IV) acetate hydroxide as the metal precursor, polyvinylpyrrolidone as the capping agent, and deionized water as a solvent. The chemicals were mixed and stirred to form a homogeneous solution and hereafter directly underwent calcination to attain the pure nanocrystalline powder, which was confirmed by FTIR, EDX, and XRD analyses. The control over the size and optical properties of nanoparticles was achieved through changing in calcination temperatures from 600 to 900°C. The obtained average particle sizes from XRD spectra and TEM images showed that the particle size increased with increasing calcination temperature. The optical properties which were investigated using a UV-Vis spectrophotometer showed a decrease in the band gap energy with increasing calcination temperature due to the enlargement of the particle size. These results prove that, by eliminating drying process (24 h) in the present thermal treatment method, size-controlled zirconia nanoparticles were conveniently manufactured with a reduction of synthesize time and energy consumption, suitable for large-scale fabrication.